2020
DOI: 10.1007/s00417-020-04866-7
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, microbiological isolates, and antibiotic susceptibilities in culture-proven pediatric endophthalmitis: a 9-year review

Abstract: Purpose To analyze the etiology, microbiological isolates, and antibiotic susceptibilities of endophthalmitis in pediatric patients. Methods Patients aged < 18 years with culture-positive endophthalmitis in Zhongshan Ophthalmic Center between January 2010 and December 2018 were included retrospectively. Results A total of 127 patients (127 eyes) were included, and 108 (85%) had posttraumatic endophthalmitis. Streptococcus (21.4%), coagulase-negative Staphylococcus (14.5%), Aspergillus (6.9%), and Bacillus cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
3
7
0
1
Order By: Relevance
“…Moloney et al reported that the sensitivity of gram-negative organisms to ceftazidime was 100%. 2 Recent studies from southern China reported that gram-positive cocci showed a relatively higher susceptibility to cephalosporins (~90%), 9 , 20 while the sensitivity of gram-negative bacteria to cefotadine was 66.67% and cefuroxime was 45.95% in our study. Hence, cephalosporins as first-line agents in the empirical treatment of endophthalmitis need to be vigilant.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Moloney et al reported that the sensitivity of gram-negative organisms to ceftazidime was 100%. 2 Recent studies from southern China reported that gram-positive cocci showed a relatively higher susceptibility to cephalosporins (~90%), 9 , 20 while the sensitivity of gram-negative bacteria to cefotadine was 66.67% and cefuroxime was 45.95% in our study. Hence, cephalosporins as first-line agents in the empirical treatment of endophthalmitis need to be vigilant.…”
Section: Discussionsupporting
confidence: 40%
“…At present, topical fluoroquinolones have been used widely as the first-line eye drops for prevention and treatment of infectious eye disease because of their broad spectrum of activity and low toxicity. The sensitivity of levofloxacin to gram-positive bacteria was disclosed to be as high as 82.3%-96.8% 19 , 20 in southern China and 77.5% in Miami. 22 In this study, however, it was only 51.67%, which was much lower than gatifloxacin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among patients with streptococcal endophthalmitis, Streptococcus pneumoniae , viridans group streptococcus and group B β-haemolytic streptococcus were the main isolates, although the dominant isolates varied in different studies [ 8 11 ]. Previous studies have focused on paediatric post-traumatic endophthalmitis caused by all pathogens [ 12 14 ]. They found that the streptococcus species was a common cause of post-traumatic endophthalmitis in children.…”
Section: Introductionmentioning
confidence: 99%
“…The foundation of the treatment for bacterial endophthalmitis is focal and systemic administration of antibiotics; vitrectomy is performed if the endophthalmitis is severe. Unless the patient receives appropriate treatment early in the disease, it causes irreversible damage to the retina, which results in a high probability of vision loss [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%